Arthroscopic Wafer Procedure for Ulnar Impaction Syndrome in an Intact Triangular Fibrocartilage Complex - Choudhury, Muntasir Mannan; Sajeev, Suraj; Sheng, Brandon Yew Bao; Wijetunga, Dashishka Thanuranga; Chin, Andrew Yuan Hui (Journal of Wrist Surgery, 2023)
Ulnocarpal impaction or ulnar abutment symptom occurs secondary to abnormal load bearing on the ulnar side of the wrist leading to pain symptoms and degeneration of the structures of the ulnocarpal joint.The two classical surgical methods used to address this problem are ulnar shortening osteotomy and the wafer procedure, which can either be open or arthroscopic. With the advent of arthroscopy, with surgeon harboring arthroscopy skills, arthroscopic wafer resection has been intensely popularized which requires a central perforation of the triangular fibrocartilage to approach the ulna dome through the ulnocarpal joint.So, what happens in symptomatic patients with ulnocarpal abutment with an intact triangular fibrocartilage complex who have failed conservative management. Do we perform an open procedure or do we create a perforation in the central disc of the triangular fibrocartilage complex to expose the ulnar dome? Or do we just do an ulnar shortening osteotomy?Here, we describe our arthroscopic technique of conducting arthroscopy in the narrow confines of the space below the triangular fibrocartilage complex above the ulnar dome to carry out an arthroscopic wafer procedure in a triangular fibrocartilage complex with no central perforation. The procedure can produce results similar to those of the classical arthroscopic wafer procedure described explicitly in the literature.
Keywords: arthroscopy; ulnar impaction; abutment; neutral variance; intact triangular fibrocartilage; complex; wafer